A Mixed-Methods Analysis of the 7P Marketing Mix and Outpatient Visit Interest at a Regional Public Hospital in Indonesia - Azwan Rahmadhan Putra; Edi Prasetyo; Mia Mariani; Dicky Budiman (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Public hospitals frequently face challenges in maintaining competitiveness due to sub-optimal service delivery and marketing strategies. This study examines the influence of the 7P marketing mix (Product, Price, Place, Promotion, People, Process, Physical Evidence) on public interest in utilizing outpatient services at RSUD Bengkalis. Employing a mixed-methods approach with a sequential explanatory design, this research integrates quantitative analysis via multiple linear regression with qualitative insights derived from fishbone diagrams. Primary data were collected from general-paying patients through structured questionnaires, followed by in-depth qualitative interviews. Quantitatively, simultaneous analysis reveals that all seven marketing mix elements significantly influence visit interest, with an Adjusted R² value of 81%, indicating high predictive power. Partially, Product, Place, People, and Physical Evidence exert a positive and significant impact on patient interest. Conversely, Price, Promotion, and Process show no statistically significant effects. Qualitative findings clarify that the insignificance of Process and Promotion stems from operational barriers, specifically inefficient manual queuing systems and restricted promotional outreach for specialized services targeting general patients. In conclusion, while the hospital’s core service offerings, accessibility, personnel, and infrastructure successfully attract patients, administrative inefficiencies and weak marketing limit its full potential. To enhance public interest and institutional competitiveness, the management of RSUD Bengkalis must prioritize the digital transformation of administrative and registration workflows, streamline the patient flow, and consistently improve staff hospitality to foster sustainable patient loyalty.